Forgetting (Al-Nisyān) Therapy: An Islamic Insight - Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi (SCAD Independent, 2023)
The capacity of memory in the brain to store, process, and recall information is truly a wondrous blessing. Forgetfulness may be a blessing from Allah to make life easier by allowing humans to forget bad events and shocks from the past. However, increased forgetfulness can lead to issues such as forgetting the Quran and other important information and being unable to concentrate. The questions that arose were how forgetfulness hinders humans in a variety of situations and circumstances, as well as its impact on living a healthy life. Using a descriptive qualitative method, this study investigated how Islam explains forgetting, its causes, and its cures from a scientific and spiritual standpoint. This study also revealed treatments that can be done to overcome this disease and circumvent negative impressions. This article found some tips to strengthen memory, such as reciting dhikr (remembrance), maintaining a well-balanced diet, reading books, memorizing the Quran, and participating in frequent prayer, which are all excellent ways to exercise a Muslim's mind.